Hepatoblastoma in two siblings and familial adenomatous polyposis: causal nexus or coincidence? - Evers, Christina; Gaspar, Harald; Kloor, Matthias; Bozukova, Gergana; Kadmon, Martina; Keller, Monika; Sutter, Christian; Moog, Ute (Familial cancer, 2012)
Infantile and childhood hepatoblastoma (HB) occurs more frequently in children with hereditary predisposition to familial adenomatous polyposis (FAP) than in the general population. The occurrence of HB in two infant siblings is reported. The sister died of the disease. The brother survived the HB and was later diagnosed with familial adenomatous polyposis and advanced rectal cancer. He was found to carry a germline mutation of the APC gene. Presuming that the HB in the two siblings was the first manifestation of FAP we performed APC mutation analysis in DNA from archived tumour tissue of his sister and in blood samples of both parents. Surprisingly, the mutation was neither found in both parents, nor in the tissue samples of the sister. We outline the impact of this finding for genetic counselling and review the literature on FAP and HB.
Gesehen am 26.11.2018